Radzieckie lektury obowiązkowe w Polsce w latach 1945–1953 - Wołodźko-Butkiewicz, Alicja (Przegląd Rusycystyczny, 2012)
Alicja Wołodźko-Butkiewicz Uniwersytet Warszawski, Warszawa, Poland ajwolodz@uw.edu.pl СОВЕТСКОЕ ОБЯЗАТЕЛЬНОЕ ЧТЕНИЕ В ПОЛЬШЕ (1945–1953) Резюме В статье обсуждается польская культурная политика первого послевоенного десяти-летия; до смерти Сталина все больше нарастала ее зависимость от советской идео-логии. Это выразилось не только в возникновении таких организаций как «Общество польско-советской дружбы» и журналов «Przyjaźń» , «Język Rosyjski» или «Literatura Radziecka» (издаваемая в Москве), но прежде всего — в деятельности издательств. Высокими тиражами издавалась новейшая советская литература, при чем многие ее произведения были включены в обязательный список школьного чтения. Польские школьники должны были знакомиться с биографиями советских вождей, фрагментами сочинений Сталина, и читать романы о положительных советских героях — прежде всего Как закалялась сталь Николая Островского и Молодую гвардию Александра Фадеева. Возникла межиздательская серия «Библиотека лауреатов сталинскoй премии», куда вошли такие соцреалистические, обширные по объему романы как Далеко от Москвы Василия Ажаева, Кавалер золотой звезды Семена Бабаевского и Счастье Петра Павленко. В эпоху oттепели их стали называть лакировочными, так как были далеки от правдивого отражения действительности. Сегодня к этому забытому кругу чтения все чаще обращаются историки литературы и культурологи, отыскивая в нем коды главных категорий советской культуры. SOVIET REQUIRED-READING BOOKS IN POLAND 1945–1953 Summary The article discusses Polish cultural policy of the first post-World War II decade which was marked by an increasing Soviet ideological indoctrination. This manifested not only in establishing in Poland organizations such as Polish-Soviet Friendship Society, publication of Russian-themed periodicals „Friendship” and „Russian Language” as well as distribution in Poland of Moscow-printed „Soviet Literature”, but most of all — in the policies of Polish publishing houses. They printed in high volumes school-mandatory Soviet books for children and youth (excerpts from Stalin’s works, biographies of Soviet heads of state, „positive hero” novels, e.g. Nikolay Ostrovsky’s How the Steel Was Tempered, Alexandr Fadeyev’s The Young Guard) and many schematic socrealistic works of literature. They also published, under the umbrella of a book series „The Winners of the Stalin Prize in Literature”, novels such as Vasily Azhayev’s Far From Moscow, Semyon Babayevsky’s Cavalier of the Gold Star or Piotr A. Pavlenko’s Happiness considered as early as the Thaw exemplary of the so-called „varnishing” and state-mandated optimism. Nowadays, these forgotten, and since 1990s also openly ridiculed, books are increasingly becoming objects of research of historians of literature and culture. As they were created according to certain, predetermined patterns, the books reveal the main codes of the Soviet culture.